Weaving in stones : garments and their accessories in the mosaic art of Eretz Israel in Late Antiquity - Steinberg, Aliza (Archaeopress Archaeology, 2019)
This book, copiously illustrated throughout, studies the garments and their accessories worn by some 245 figures represented on approximately 41 mosaic floors (some only partially preserved) that once decorated both public and private structures within the historical-geographical area of Eretz Israel in Late Antiquity.